Effect of low-energy extracorporeal shock wave on vascular regeneration after spinal cord injury and the recovery of motor function [Retraction] - Wang L (Dove Medical Press, 2016)
Wang L, Jiang Y, Jiang Z, Han L. Effect of low-energy extracorporeal shock wave on vascular regeneration after spinal cord injury and the recovery of motor function. Neuropsychiatr Dis Treat. 2016 Aug 31;12:2189–2198. doi: 10.2147/NDT.S82864.This article was found to have plagiarized the content of:Low-energy extracorporeal shock wave therapy promotes vascular endothelial growth factor expression and improves locomotor recovery after spinal injury published in the Journal of Neurosurgery in 2014 (J Neurosurg. 121: 1514–1525, 2014).Accordingly, Dr Pinder, Editor-in-Chief of Neuropsychiatric Disease and Treatment has decided to issue a Retraction notice and advise the academic supervisors of Dr Wang et al of this matter. This Retraction relates to